2020
DOI: 10.3390/microorganisms8101474
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Beneficial Properties of the Bacteriocinogenic Enterococcus faecium ST10Bz Strain Isolated from Boza, a Bulgarian Cereal-Based Beverage

Abstract: The bacteriocin-producing strain Enterococcus faecium ST10Bz, isolated from boza, a Bulgarian cereal-based beverage, exhibited strong activity against Listeria strains, vancomycin-resistant and other Enterococcus strains, but not against most of the other lactic acid bacteria (LAB) strains included in the test panel. Bacteriocin ST10Bz was proven as a stable antimicrobial, even after exposure to various environmental conditions, including varying pH values, temperatures, and commonly used chemicals in industry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 79 publications
(93 reference statements)
1
10
0
Order By: Relevance
“…Bacteriocins produced by P. acidilactici ST3522BG and P. pentosaceus ST3633BG were highly active against L. monocytogenes, L. innocua and Enterococcus spp., including more than 20 Enterococcus strains previously characterized as vancomycin-resistant (Table 1). In addition, it was shown that vancomycin-resistant enterococci, sensitive to the applied two bacteriocins, generated positive results for carrying vanA, a plasmid associated antibiotic resistance gene (data not shown, an experiment performed according to recommendations of Valledor et al, 2020). The spectrum of bacteriocin activity is important for the characterization of new antimicrobial proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteriocins produced by P. acidilactici ST3522BG and P. pentosaceus ST3633BG were highly active against L. monocytogenes, L. innocua and Enterococcus spp., including more than 20 Enterococcus strains previously characterized as vancomycin-resistant (Table 1). In addition, it was shown that vancomycin-resistant enterococci, sensitive to the applied two bacteriocins, generated positive results for carrying vanA, a plasmid associated antibiotic resistance gene (data not shown, an experiment performed according to recommendations of Valledor et al, 2020). The spectrum of bacteriocin activity is important for the characterization of new antimicrobial proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Selection of L. monocytogenes as principal test organism in screening for producer(s) of antimicrobial metabolites strains was based on relevance of that food-borne pathogen for human and other animals' health. L. monocytogenes is highly contagious microorganisms, able to survive in low pH and under refrigeration, and was listed as having "zero tolerance" for different food products and by several countries [6,32,35]. All selected potential bacteriocin producers were pre-identified as Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA previously isolated from the evaluated strains was subjected to PCR analysis for investigating the presence of vancomycin resistance genes vanA (vanAB/F: 5 -GTA GGC TGC GAT ATT CAA AGC -3 ; vanA/R: 5 -CGA TTC AAT TGC GTA GTC CAA -3 ), vanB (vanAB/F: 5 -GTA GGC TGC GAT ATT CAA AGC -3 ; vanB/R: 5 -GCC GAC AAT CAA ATC CTC -3 ), vanC (vanC/F: 5 -ATC CAA GCT ATT GAC CCG CT -3 ; vanC/R: 5 -TGT GGC AGG ATC GTT TTC AT -3 ), vanD (vanD/F: 5 -TGT GGG ATG CGA TAT TCA A -3 ; vanD/R: 5 -TGC AGC CAA GTA TCC GGT AA -3 ), vanE (vanE/F: 5 -TGT GGT ATC GGA GCT GCA G -3 ; vanE/R: 5 -GTC GAT TCT CGC TAA TCC -3 ) and vanG (vanG/F: 5 -GAA GAT GGT ACT TTG CAG GGC A -3 ; vanG/R: 5 -AGC CGC TTC TTG TAT CCG TTT T -3 ) previously reported by Valledor et al [35]. PCR products were separated on 2.0% (w/v) agarose gels in 1x TBE and visualized as described before.…”
Section: Detection Of Vancomycin Resistant Genesmentioning
confidence: 99%
“…The extracted DNA of the selected strains was tested for the presence of the following virulence-related genes: gelatinase (gelE), hyaluronidase (hyl), aggregation substance (asa1), enterococcal surface protein (esp), cytolysin (cylA), endocarditis antigen (efaA), adhesion of collagen (ace), vancomycin resistance genes (vanA and vanB (by two different sets of primers) and vanC, vanD, vanE and vanG), histidine decarboxylase (hdc1 and hdc2), tyrosine decarboxylase (tdc) and ornithine decarboxylase (odc), using the PCR primers and conditions described by Todorov et al (2017) and Valledor et al (2020). The amplified products were separated and stained as described before in this paper.…”
Section: Screening For the Presence Of Virulence And Antibiotic Resistance Genesmentioning
confidence: 99%